2260. HIV Transplantation Awareness and Attitudes Following Implementation of the HOPE Act. (26th November 2018) - Bansal, Ankit; Willig, James; Erdmann, Nathan
Abstract: Background: As HIV infection has evolved from a highly morbid diagnosis to a functionally chronic condition, comorbid conditions including liver and kidney failure have become more prevalent. Limited organ availability prevents many persons living with HIV (PLWH) from having an opportunity for transplantation. Inclusion of PLWH as organ donors is uniquely suited to increasing access to life saving grafts. Here, we sought to assess the awareness of the HOPE Act in PLWH, and determine whether providing information on the HOPE Act and HIV to HIV transplantation increased support for becoming an organ donor. Methods: Using a computer interface, we surveyed 200 patients in an HIV clinic and assessed their awareness of the HOPE Act and attitudes toward transplantation. Incorporated into the survey was a brief explanation of the HOPE Act and background into HIV to HIV transplantation. The information provided during the survey functioned as an intervention, and we again asked participants about their willingness to be an organ donor at the end of the survey. Results: Over 75% of survey participants indicated support for organ transplantation in general, but less than 50% participants were willing to be listed as organ donors. 85% responded that they did not know whether PLWH were allowed to be an organ donor, and 94% were not familiar with the HOPE Act. However, 80% of respondents reported they would be willing to accept an organ from an HIV-infected donor. Support for organ donation increased to 60% after information about the HOPE Act and HIV transplantation was provided during the survey. Comparison of responses from before and after the intervention resulted in a kappa statistic of 0.42, indicating a change in opinion before and after the survey. Conclusion: HIV-infected persons are at particularly high risk for organ failure. Most HIV-infected patients were unaware of HIV to HIV transplantation as a possibility and were reluctant to agree to become an organ donor. However, with this very brief, passive intervention, attitude toward transplantation improved. These findings suggest that informing PLWH about the HOPE Act and becoming an organ donor would be beneficial as HIV to HIV transplantation becomes more available. Disclosures: All authors: No reported disclosures.